Evaluating the potential of tasks to occasion mathematical creativity: definitions and measurements. Issue 3 (2nd September 2018) - Levenson, Esther; Swisa, Riki; Tabach, Michal
ABSTRACT: Creativity is often characterised by three components: fluency, flexibility, and originality. Specifically, in the mathematics classroom, in order to promote these aspects of creativity, educators recommend engaging students with multiple-solution tasks and open-ended tasks. In the past, various methods were used to measure fluency, flexibility and originality. This study raises questions and dilemmas regarding these methods and measures, and illustrates the complexity of these issues with data collected from fifth-grade students engaging with three such tasks. Some of the questions raised are related to differences between multiple-solution tasks and open-ended tasks, and between creative process and creative outcomes. In addition, the gap between the potential embedded within a task and its actual results is discussed.